1999
DOI: 10.1101/gr.9.9.830
|View full text |Cite
|
Sign up to set email alerts
|

Compound Microsatellite Repeats: Practical and Theoretical Features

Abstract: Most linkage and population genetic studies that use microsatellites assume that the polymorphism observed at these loci is due simply to variation in the number of units of a single repeat. Variation is far more complex, however, for the numerous microsatellites that contain interruptions within the repeat or contain more than one type of repeat. We observed that for D18S58, a compound microsatellite containing (CG) m , as well as (CA) n repeats, the apparent length of certain alleles varied between genotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Studies in other taxa have similarly shown that the representation of motifs in compound repeats deviates strongly from random expectation (Bull et al, 1999;Kruglyak et al, 2000). These patterns point to as yet unknown mutational processes of presumably neutral dinucleotide repeats.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies in other taxa have similarly shown that the representation of motifs in compound repeats deviates strongly from random expectation (Bull et al, 1999;Kruglyak et al, 2000). These patterns point to as yet unknown mutational processes of presumably neutral dinucleotide repeats.…”
Section: Discussionmentioning
confidence: 90%
“…The same is true for the peculiar and taxonspecific polarity. While in Bombina most TA-CA microsatellites have a TA motif at the 5 0 end, the opposite is true for yeast (Kruglyak et al, 2000), while no trend is seen in humans (Bull et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The high frequency of compound microsatellites in coffee is unusual since they tend to be rare in other plant genomes they tend to be rare (Cardle et al 2000). It is interesting that (AC) n (CT) n , the most common compound microsatellite in coffee, is also a very common compound microsatellite in humans (Bull et al 1999). Baruah et al (2003) also carried out hybridization experiments with radiolabelled di-and trinucleotide repeats; they do not describe the total number of positive clones that hybridized to each oligonucleotide but identified a total of eight dinucleotide repeats and only one trinucleotide repeat microsatellite, which suggests a lower frequency of trinucleotide repeat microsatellites in the coffee genome.…”
Section: Identification and Characterization Of Microsatellite Sequencesmentioning
confidence: 99%
“…Moreover, different dinucleotide motifs have a strikingly different length distribution in the human genome [8], possibly due to motif-specific differences in the efficacy of mismatch-repair [25]. A significant number of uninterrupted compound repeats (> 30, 000) such as (TG) m -(TA) n , with both m and n ≥ 5 repeat units, occur in the human genome (Sainudiin and Durrett unpublished re-sults); their evolutionary dynamics are complex [5] and not well understood. A further complication to measuring microsatellite variability is that insertions/deletions in the flanking regions can also affect the PCR fragment length (see e.g.…”
Section: Introductionmentioning
confidence: 99%